Assessment of Lead, Cadmium, Nickel, and Chromium Residues in Camel Meat and Offal - Darwish, Wageh S.; Tharwat, Ahmad E.; Elkady, Samah Ahmad; Fakhry, Basma A. (Journal of Advanced Veterinary Research, 2023)
In several nations of the Middle East, camel meat is a significant source of animal-derived protein, vitamins, and minerals. In the Arab and African continents, camels are extremely significant. The study was conducted to determine the residual levels of heavy metals (lead, cadmium, nickel, and chromium). Camel meat plays a significant role in these regions as a source of protein, but it may also contain many toxic substances as residues contamination with heavy metals, which are considered serious threats not only due to their toxicity but also because of bioaccumulation in the food chain. The average lead levels in the analyzed samples of muscles, kidneys, and livers were 0.11±0.03, 0.47±1.18, and 0.7±0.13 mg/kg, respectively. The mean concentrations of cadmium in muscles, livers, and kidneys, however, were 0.13±0.04, 0.43±0.12, and 0.85±0.34 mg/kg, respectively. While the residual chromium levels in the muscles, livers, and kidneys were, respectively, 0.1±0.45, 0.21±0.11, and 0.25±0.07 mg/kg. The residual level of all the metals in different tissues were found to be substantially different, with a p-value <0.05, whereas nickel was 0.13, 0.16, and 0.23 mg/kg. In conclusion, liver and kidneys has higher concentrations of the tested metals compared with muscles. However, the recorded concentrations of the tested metals lies within the acceptable limits set by the regulatory authorities.